Effect of almond shell addition to substrates in Phaseolus vulgaris L. (cv. Saxa) growth, and physiological and biochemical characteristics - Ivo Oliveira; Anne Meyer; Rita Silva; Sílvia Afonso; Berta Gonçalves (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose In the almond industry, the major by-product is the shell, the woody outer layer of the almond fruits. The goal of this research was to study the consequence of the incorporation of almond shell to cultivation substrates on green bean plant grown in a growth chamber. Methods Almond shell was mixed with peat (20%:80%) (AS), or used as mulch (AM) on top of the control (C) substrate (33.3%:66.6% vermiculite and peat). Evaluated parameters included green bean pod production and characteristics and their biochemical parameters, namely pigments, total phenolics and antioxidant activity, and soluble sugars and proteins, but also leaf gas exchange parameters. Results The use of almond shell as a mulch resulted in unexpected higher crop growth rate, relative leaf growth rate, and leaf area index, with similar production and dimension of pods, when compared to the control assay, with comparable amounts of phenolic compounds, antioxidant capacity, and soluble sugars and proteins, even if gas exchange parameters were negatively affected. By other hand, the data from the almond shell:peat mixture indicate important increase of carotenoid content, contrasting to the control substrate. Conclusion These results indicate that almond shell has some potential as growing medium for green bean cultivation, when mixed with peat or used as a mulch.